Biochemical parameters and pathogenesis of SARS-CoV-2 infection in vital organs: COVID-19 outbreak in Iran (2020)
With the emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) outbreak, human being certainly is witnessing its very first enormous threat in new millennium. Unexpectedly, coronavirus disease 2019 (COVID-19) spread the world leading to a constantly increasing mortality rate. The SARS-CoV-2 infection perturbs body’s vital organs function making the patients of all ages susceptible to the disease. Nevertheless, individuals developing critical illness with poor outcomes mostly were the elderly and the ones having comorbid conditions which constitute the vast majority of COVID-19 fatalities. The COVID-19 complications mostly involve respiratory, renal and cardiovascular systems, and in severe cases secondary infections leading to pneumonia and acute respiratory distress syndrome (ARDS) precede the demise of the patient. Indeed, multi-organ failure in COVID-19 patients could be a consequence of comorbidities associated with the patients. Therefore, patient’s preexisting conditions may apparently affect the disease prognosis requiring immediate attention to accurately detect and evaluate them in SARS-CoV-2 infected patients. Herein, several issues given the findings in relation to manifestations of body’s vital organs along with potential diagnostic blood factors in SARS-CoV-2 infection will be addressed. It is hoped that the review help to more comprehensive understanding of this very complex disease.